Zygomatic abscess – a rare sequalae of otitis media - Muhammad, Athierah; Hussein, Nurfarissa; Mohari, Norhaslinda; Azwal, Norazwani (FAKULTI PERUBATAN DAN SAINS KESIHATAN, UPM, 2023)
A zygomatic abscess is a rare complication of acute otitis media. However, over the past two decades, such cases have increased, which might be linked to the rise of antibiotic abuse and antibiotic resistance. Diagnosing and treat- ing a zygomatic abscess is essential as a delay in proper treatment can cause potential harm to the patient. The ideal treatment for these cases is modified radical mastoidectomy with abscess drainage.